2010
DOI: 10.1021/es100130h
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Absorption and Optimization of Solar Photocatalytic Reactors for Environmental Applications

Abstract: This study provides a systematic and quantitative approach to the analysis and optimization of solar photocatalytic reactors utilized in environmental applications such as pollutant remediation and conversion of biomass (waste) to hydrogen. Ray tracing technique was coupled with the six-flux absorption scattering model (SFM) to analyze the complex radiation field in solar compound parabolic collectors (CPC) and tubular photoreactors. The absorption of solar radiation represented by the spatial distribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
96
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(110 citation statements)
references
References 33 publications
10
96
0
4
Order By: Relevance
“…For this reactor, it was assumed perfect mixing and removal percentages of MB (%Degr) as response variable (19):…”
Section: Materials and Equipmentmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reactor, it was assumed perfect mixing and removal percentages of MB (%Degr) as response variable (19):…”
Section: Materials and Equipmentmentioning
confidence: 99%
“…Typically, the interpretation of the experimental results is based on t 30w (19), the treatment time (20), the incident radiation within the reactor, and the photon flux absorbed by the catalyst. However, these parameters interact and yield erroneous conclusions, which is impractical given that the reactor is comprised of illuminated and non-illuminated areas.…”
Section: Mass Balance In the Dark Zonementioning
confidence: 99%
“…Such nanophotocatalysts have also been used for the treatment of winery wastewater using a photocatalytic reactor [68]. Today, the use of photoreactors of pilot plants has grown quickly in the development and use of different kinds of photocatalytic reactors, especially to be used with solar radiation [69][70][71].…”
Section: Photo-degradation Of Pollutants and Hazardous Compoundsmentioning
confidence: 99%
“…This pH value was chosen given that several authors have already reported the influence of pH on TiO2-mediated photocatalytic degradation of AMX and found minimal influence in the near-neutral pH range (Elmolla and Chaudhuri 2010b;Klauson et al 2010;Dimitrakopoulou et al 2012). The suspended catalyst load for photocatalysis was 0.5 g L −1 of TiO2, which is able to absorb all solar UV photons considering an internal photoreactor tube diameter of 46.4 mm (Colina-Márquez et al 2010). Thirty minutes after TiO2 addition, another sample was taken to determine the AMX adsorption onto the catalyst surface (which was found out to be less than 2 % in average), and then the CPCs were uncovered in order to begin the photocatalytic experiments.…”
Section: Solar Pilot Plantmentioning
confidence: 99%
“…However, to the best of our knowledge, none so far have neither applied compound parabolic collectors (CPC) as photoreactors, nor have studied the influence of the individual presence of common occurring inorganic ions on the degradation of amoxicillin in aqueous solution. Theoretical and experimental studies (Fernández et al 2005;González et al 2009;Vilar et al 2009;Colina-Márquez et al 2010) have shown that CPCs are highly efficient on collecting solar radiation, so they are considered the best choice for different solar photocatalytic processes (Malato et al 2002). Thus, the main objective of this work was to study the enhancement of the photocatalytic degradation of AMX in a CPC pilot plant, promoted by the presence of suspended TiO2 and natural sunlight, when compared with solar photolysis.…”
Section: Introductionmentioning
confidence: 99%